An introduction to the multidimensional real-time economic modeling - Mario Arturo Ruiz Estrada; V G R Chandran; Muhammad Tahir (Contemporary Economics, 2016)
This article proposes a new economic modeling theoretical framework known as multidimensional real-time economic modeling (MRTE-Modeling). The model is an important tool that economists and educators can use to demonstrate the multidimensional aspects of economic behavior. MRTE-Modeling facilitates the analysis of a series of complex and dynamic economic problems that can affect market behavior from a multidimensional perspective. The proposed MRTE-Modeling framework is based on the uses of an alternative mathematical modeling framework, multidimensional graphical modeling approach, and computer algorithm and, thus, allows the possibility to transition from 2-dimensional economic dynamic modeling to multidimensional real-time economic modeling. Therefore, the main objective of using the proposed experimental model in the field of economics is to analyze different macroeconomic scenarios to monitor and provide a warning of possible unexpected economic failure(s). The proposed alternative experimental model is based on the application of Econographicology. Hence, our model is expected to offer policy makers and researchers new analytical tools to study the impact and trend of economic failures in the economy of any country from a new perspective.
Keywords: Y20; 330; economic modeling; real-time analysis; multidimensional coordinate spaces; econographicology